Towards atraumatic cochlear implant insertion monitoring using a hydraulic-based, cost-effective intracochlear pressure probe - Bernardi, Walter; Weder, Stefan; Mantokoudis, Georgios; Caversaccio, Marco; Aebischer, Philipp (Frontiers in Surgery, 2025)
PurposeCochlear implantation is an established treatment for severe sensorineural hearing loss, but residual preoperative hearing is often lost during the surgery, in part due to intracochlear pressure transients that damage cochlear hair cells. To enable real-time monitoring of insertion dynamics, we propose a cost-effective, remote pressure probe for continuous measurement of intracochlear pressure during cochlear implant surgery.MethodsThe probe comprises a steel cannula placed at the round window, transmitting intracochlear pressure to a remotely positioned pressure sensor, thereby preserving surgical access.ResultsWe demonstrated effective pressure transmission across different cannula sizes (between 0.21 and 0.41 mm), validating the probe concept. In an artificial temporal bone model, sensor measurements during cochlear implant insertion showed a strong correlation with reference measurements of intracochlear pressure.ConclusionWe developed and validated a novel, cost-effective, hydraulic probe for atraumatic, real-time monitoring of intracochlear pressure during cochlear implant insertion via a round-window approach. Thereby, the proposed probe offers a feasible, quantitative, directly interpretable metric on cochlear implant insertion.